Penggunaan Ekstrak Rimpang Lengkuas untuk Mengendalikan Busuk Leher Akar pada Tanaman Terong (Solanum Melongena L.) - Juni Safitri Muljowati; Eddy Tri Sucianto (Fakultas Biologi | Universitas Jenderal Soedirman, 2012)
A research to find antifungal activity of galanga rhizome (Alpinia galanga L.) on Sclerotium rolfsii as the causal agent of white mold and stem rot disease on eggplant has been done. The galanga extract was obtained by extracting the rhizome using ethanol solvent. The experiment design was Completely Randomized Design (CRD) in a factorial pattern, involving two factors, i.e. the rhizome extract concentration (E) with six levels of 0%, 5%, 10%, 15%, 20%, and 25%; and application time (W) with two levels of three days interval and seven days interval. The result showed that the best extract concentration was 20% that was applied in three days interval.